Synonyms Analysis in Economic News about the Inflation Crisis in CNN Arabic Online Media - Endah, Sofie; Aqila, Fariz; Nisa, Zahrotun; Alvan, Ridha Savira Putri (Journal of Arabic Language Studies and Teaching, 2023)
This study aims to describe, understand, analyze, and discover the types of synonyms and collect synonyms in economic news about inflation on CNN Arabic online media. The research object used is synonyms containing phrases, words, and the number of sentences that indicate the means of word relations in synonyms. The qualitative descriptive method is the method used in this study. The data collection technique in this study was the library method. The data source was taken from Arabic-language online media, namely CNN Arabic. The results of this study indicate that a total of 43 synonyms were found with details: the type of perfect synonymy (الترادف الكامل), there are ten synonyms, the type of near synonymy (شبه الترادف) there are 12 synonyms, the type of semantic relation (التقارب الدلالي) there are ten synonyms, synonyms, types of التفاوت في الخصوص there are as many as two synonyms, types of التفاوت في القوة there are as many as four synonyms, types of التفاوت في الملامح there are as many as five synonyms, and 0 for types of التفاوت في العموم.